Factors influencing repayment performance of livestock farmers: An application of discriminant function analysis* - PANDIAN, A SERMA SARAVANA; SELVAKUMAR, K N; KUMAR, B GANESH (The Indian Journal of Animal Sciences, 2014)
The linear discriminant function analysis was used to identify the variables that are important in cliscriminating between non-defaulters and defaulters. Independent variables (15) - educatiorial level oftne borrower-fanner, family size, political influence. amount of loan borrowed, distance from credit institution, way of marketing, repayment capacity, income tram animal husbandry, total income of the family, family consumption expenditure; land holding category, caste and total asset of the fumily, were included for analysis. The results of the step-wise selection revealed the educational levd of the borrower. political infiuence, loan amount, repayment capacity and family consumption expenditure and these were the important significant variables, which discriminatqd non-defaulters from defaulters. The results of the classification of cases based on the score obtained by the discriminant function had shown that among the non-defaulters 71.9 % were predicted correctly by the model, while among the defaulters 87.9% were identified correctly. In total 80 percent of the original grouped cases were correctly classifled by the model.